Imperialism, Colonialism and Racism in Joseph Conrad's Heart of Darkness: A Postcolonial Approach - Hasan, Mariwan; Ahmed, Lona; Muhammad, Roman (LPPM Universitas Advent Indonesia, 2021)
It is not easy to explore the inner side and the hidden nature of human beings. It is also what has strengthened the relationship between human beings and the issue of imperialism and colonialism and the final stage of colonialism which leads to racism. This paper deals with colonialism, imperialism, and racism in Joseph Conrad's novella, Heart of Darkness. The three stages colonizers implement during colonizing African countries. Modern age and modern literature are shed light on in general and more particularly, modern novel is focused on as it is necessary for the analysis of the novel. Then the terms of colonialism, imperialism, and racism are explored in Heart of Darkness as these are interrelated words having close links to colonization. A postcolonial approach is used to analyze the novella.